2015
DOI: 10.1016/j.bbacli.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of circulating microparticles in patients with chronic heart failure

Abstract: AimThe study aim was to evaluate whether circulating microparticles with apoptotic or non-apoptotic phenotypes are useful for risk assessment of 3-year cumulative fatal and non-fatal cardiovascular events in CHF patients.MethodsThe incidence of fatal and non-fatal cardiovascular events, as well as the frequency of occurrence of death from any cause in a cohort of 388 patients with CHF during 3 years of observation was studied prospectively. Circulating levels of NT-pro brain natriuretic peptide (NT-pro-BNP), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
0
34
1
1
Order By: Relevance
“…Consequently, uric acid may consider as an endogenous regulator of vascular repair system that undoubtedly opens new sign on the role of uric acid metabolism as integrative asset explaining an impact of various comorbidities on a risk of HF manifestation. As an evidence of the opinion it has been allowed presenting data, which confi rm higher predictive value of elevated SUA in HF patients beyond etiology of disease, cardiac pump function, traditional risk factors and estimated glomerular fi ltration rate [24][25][26]. Interestingly, large numbers of clinical and observational studies have shown that elevated SUA levels are associated with reduced survival in in-patients and outpatients with several phenotypes of chronic HF, as well as in acute / actually decompensated HF [27][28][29].…”
Section: Short Communicationmentioning
confidence: 99%
“…Consequently, uric acid may consider as an endogenous regulator of vascular repair system that undoubtedly opens new sign on the role of uric acid metabolism as integrative asset explaining an impact of various comorbidities on a risk of HF manifestation. As an evidence of the opinion it has been allowed presenting data, which confi rm higher predictive value of elevated SUA in HF patients beyond etiology of disease, cardiac pump function, traditional risk factors and estimated glomerular fi ltration rate [24][25][26]. Interestingly, large numbers of clinical and observational studies have shown that elevated SUA levels are associated with reduced survival in in-patients and outpatients with several phenotypes of chronic HF, as well as in acute / actually decompensated HF [27][28][29].…”
Section: Short Communicationmentioning
confidence: 99%
“…Acting through several intracellular pro-survival regulators (hypoxia induced factor-1α, Akt / eNOS signaling) EPC-depending cytokines are able mediate cytoprotective effects on the target cells in injured tissues [9]. In this context, CV risk factors including diabetes, obesity, impaired fasting glucose, hypothyroidism, hyperurikemia may induce EPC dysfunction determined as lowering EPC number and weak their functionality [10][11][12][13]. As a result EPC dysfunction may precedes manifesting endothelial dysfunction and CV diseases through worsening vascular repair capability [9,14].…”
mentioning
confidence: 99%
“…In this context, CV risk factors including diabetes, obesity, impaired fasting glucose, hypothyroidism, hyperurikemia may induce EPC dysfunction determined as lowering EPC number and weak their functionality [10][11][12][13]. As a result EPC dysfunction may precedes manifesting endothelial dysfunction and CV diseases through worsening vascular repair capability [9,14]. On the other hand, EPC dysfunction could preview CV diseases and even CV risk factors, although there is no a clear explanation of the phenomenon [14][15][16].…”
mentioning
confidence: 99%
See 2 more Smart Citations